Kirchner and Time – An Analysis of Linear and Nonlinear Time in Leon Kirchner's Interlude I - Twitchell, Adriana Jarvis; Barros, Guilherme Sauerbronn (Revista Vórtex, 2019)
This article aims to analyze temporality in Leon Kirchner's Interlude I for solo piano, in light of Jonathon Kramer's book The Time of Music. The first section serves as an introduction to the composer – his biography, influences, and compositional style. The following section introduces Jonathon Kramer's book and his concepts of linear and nonlinear time in music. Thereafter an analysis of aspects of the Interlude's linear time, as defined by Kramer, is presented, including linearity manifest through developing variation, step-wise motion, tonal references, changes in tempo, flexion count changes, and transpositions. The next section seeks to examine manifestations of nonlinear time in the Interlude, such as balance and recapitulation, and discusses the implications of Kramer's nonlinear moment time. The conclusion summarizes interactions between linearity and nonlinearity in the Interlude.